Priming interaction to foster reading engagement among tertiary level ESL students / Puteri Rohani Megat Abdul Rahim - Abdul Rahim, Puteri Rohani Megat (2014)

(untitled)
This study examines the link between an interactive pedagogical approach and university students‘ engagement in second language reading. Recognizing the importance of university students acquiring effective reading skills, a considerable number of research on second language reading has been focussing on ways to facilitate students‘ engagement in reading through the employment of reading strategies. However, minimal research has explored lecturers‘ interaction as a strategy to promote students‘ reading engagement. This dissertation explores the potential usefulness of priming interaction in fostering students‘ reading engagement. The qualitative case study approach was employed in an ESL reading class at a university, over a period of 14 weeks. The study explored ways of strategically fostering interaction throughout the teaching and learning process. The methods used to gather data were observations, semi-structured interviews, collection of documents such as the in-class letters, out-of class letters; pre-teaching and post-teaching questionnaires; as well as the instructor‘s lesson plans and reflective notes. The data obtained from these sources were analysed and later triangulated using the constant comparative method. The findings from this research show that students responded positively when the learning environment provides opportunities for them to interact, to dialogue and to give voice to their learning experiences. In addition, the role of interaction has contributed to the participants‘ reading engagement because the elements under the pedagogical approach permitted the participants to experience reading in an engaging, meaningful manner. The primed interactions stimulate the students to become more aware and critical of their assumptions during the reading process. When students are given opportunities to experience concrete interactions through a planned and strategic pedagogical approach and when the learning environment is built on trust and care, their interest to learn seem to be fostered. However, findings also reveal challenges in planning interactions iii strategically because of the students‘ culture of learning. As such the study is significant in advancing the knowledge base on teaching reading to ESL tertiary level students and it highlights the potential value of considering interaction strategically primed to foster engagement in reading.